The influence of internal control systems, information technology utilization and organizational commitment on the performance of local government institutions - Otniel Safkaur; Lusianti Rombe; Novalia H Bleskadit (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study aims to determine the influence of the internal control system, the use of information technology, and organizational commitment to the performance of Jayapura City government agencies. This type of research is quantitative research using a causal associative design. The data analysis method used in this study is multiple regression analysis with the help of SPSS version 22. The population in the study was 23 OPDs within the jayapura city offices and agencies, the research samples were the Head of the Office/ Agency/ Secretary, the Head of the Planning and Reporting Program Subdivision, as well as staff with data sources obtained through the results of filling out questionnaires. Based on the results of the partial research conducted, it can be seen that the internal control system, the use of information technology and organizational commitment have a significant effect on the performance of government agencies. And simultaneously the internal control system, the use of information technology, and organizational commitment have a significant effect on the performance of government agencies.